(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the distinctive component features of the phraseological units used in Abdulla Qodiriy’s novel "O’tkan kunlar", their role in artistic expression, and the issues related to the translation of these linguistic units into English.